Road Performance Analysis of Jalan Laksamana Bintan at Hijrah Industrial Complex, Batam - Sandhi Rio Pratama; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2023)
Jalan Lakshmana Bintan, which is precisely in front of the primary school and the Hijrah industrial complex, is currently a hot topic of conversation for the people living in the area. The intersections in front of the exit of the site are often congested. This happened because the road section shrank from 2 lanes to 1 lane when passing through the site. Intersections in the right area must be equipped with signs so they are dangerous for passing people. This research uses guidelines from MKJI 1997. Data were obtained from the volume of traffic that occurs within 1 hour from 12.00-13.00 on Saturday 12,11,2022 at Jalan Laksamana Bintan, Batam, Indonesia. From the analysis, we find out that the level of services (LOS) in Jalan Laksamana Bintan road is C, so from this research, it can be concluded that Jalan Laksamana Bintan is still relatively stable during busy vehicle times.